Optical coherence tomography (OCT) - versus angiography-guided strategy for percutaneous coronary intervention: a meta-analysis of randomized trials - Wang, Yanwei; Yang, Xi; Wu, Yutao; Li, Yanqin; Zhou, Yijiang (BMC cardiovascular disorders, 2024)
Background Optical coherence tomography (OCT) guidance in percutaneous coronary intervention (PCI) has been shown to improve procedural outcomes. However, evidence supporting its superiority over angiography-guided PCI in terms of clinical outcomes is still emerging and limited. This study aimed to compare the efficacy and safety of OCT-guided PCI versus angiography‐guided PCI in patients with coronary artery disease (CAD). Methods A systematic search of electronic databases was conducted to identify randomized control trials (RCTs) comparing the clinical outcomes of OCT-guided and angiography‐guided PCI in patients with CAD. Clinical endpoints including all-cause mortality, myocardial infarction (MI), target lesion revascularization (TLR), stent thrombosis and major adverse cardiac events (MACE) were assessed. Results Eleven RCTs, comprising 2,699 patients in the OCT-guided group and 2,968 patients in the angiography-guided group met inclusion criteria. OCT-guided PCI was associated with significantly lower rates of cardiovascular death(RR 0.56; 95%CI: 0.32–0.98; p = 0.04; I 2 = 0%), stent thrombosis(RR 0.56; 95%CI: 0.33–0.95; p = 0.03; I 2 = 0%), and MACE (RR 0.79; 95%CI: 0.66–0.95; p = 0.01; I 2 = 5%). The incidence of all-cause death (RR 0.71; 95%CI: 0.49–1.02; p = 0.06; I 2 = 0%), myocardial infarction (RR 0.86; 95%CI: 0.67–1.10; p = 0.22; I 2 = 0%) and TLR (RR 0.98; 95%CI: 0.73–1.33; p = 0.91; I 2 = 0%) was non-significantly lower in the OCT-guided group. Conclusions Among patients undergoing PCI, OCT-guided PCI was associated with lower incidences of cardiovascular death, stent thrombosis and MACE compared to angiography-guided PCI. Trial registration PROSPERO registration number: CRD42023484342.